Begleitverletzungen bei Tuberculum-majus-Frakturen: Entstehungsmechanismus, Diagnostik, Therapie - Muhm, Markus Joachim; Arend, Susanne; Winkler, Hartmut; Ruffing, Thomas (Der Unfallchirurg, 2017)
BackgroundTo date, little attention has been given to greater tuberosity fractures (GTFs) in the literature. Several mechanisms of injury are described, but few authors report that a GTF is accompanied by a high rate of often unrecognized associated injuries.ObjectivesThe aim was to document the incidence of dislocation, to diagnose associated injuries and, based on these, these draw conclusions about the mechanism of injury concerning GTF.Patients and methodsFrom 2007-2015 the detection of a shoulder dislocation, the fracture extent (displacement, fragments, size), associated injuries, and the surgical treatment of GTF and associated injuries were documented in 46 patients with GTF who were less than 65 years of age. After detection of associated injuries by computed tomography, magnetic resonance imaging (MRI) or arthroscopy it was decided if surgery was necessary or not.ResultsShoulder dislocation was found in 46.2 % of patients with a 1-fragmentary GTF. Shoulder dislocation was found in 66.7 % of patients with a 2-fragmentary GTF and 100 % of patients with ≥3 fragments.. Typical injuries associated with dislocation were found in 90.7 %. In 52.6 % of these surgery was necessary. With or without dislocation, approximately the same prevalence of associated injuries was present (92.6 %; 87.5 %). With dislocation surgery for the associated injuries was necessary in 70.8 %; without dislocation surgery was necessary in 35.7 %.DiscussionThe reason for a GTF seems to be an anterior shoulder dislocation or partial dislocation. In multifragmentary GTF or GTF with dislocation surgery is necessary frequently; without dislocation surgery is necessary less frequently. Associated injuries should be searched for selectively. An arthroscopy could be performed for diagnosis and therapy. In a GTF that can be treated conservatively, an MRI should be performed.
Übersetzung des Titels: Associated injuries with greater tuberosity fractures : mechanism of injury, diagnostics, treatment
First online: 14 September 2016
Gesehen am 22.08.2018